Progress in the discovery of new bioactive substances from deep-sea associated fungi during 2020-2022 - Wang, Zimin; Qader, Mallique; Wang, Yufei; Kong, Fandong; Wang, Qi; Wang, Cong (Frontiers in Marine Science, 2023)
The marine environment can harbor millions of macro- and micro-organisms. These habitats have gained more attention as it was found they produce a plethora of novel secondary metabolites. Recently, marine-derived fungi have become the hotspot in drug discovery and development. Deep-sea-associated fungi are an important group of marine fungi living in the ocean below 1000 m. The extreme living environment of high pressure and low temperature mean the deep-sea-associated fungi are difficult to collect but has resulted in the evolution of the special secondary metabolic genes in them. Although the vast majority of deep-sea fungi are undiscovered and very few natural products have been reported from them compared to the fungi derived from the near and shallow sea, they are still considered to be potential prolific sources of novel bioactive compounds that are of considerable interest for new drug leads. This review will expound on the sources of strains, chemical structures, and biological activity of 184 new natural products isolated from 46 deep-sea-associated fungi, which were reported from 2020-2022.